Peningkatan Kualitas Pembelajaran Pendidikan Kewarganegaraan Melalui Penerapan Strategi Pembelajaran Aktif - Pebriyeni, Pebriyeni (Jurnal Demokrasi, 2007)
Improving the quality of learning at schools always becomes a topic in various scientific discussion of education. It might be caused by the improvement of learning quality which forms the starting point to make a good citizen. This article tries to elaborate how to improve the quality of civics learning through the implementation of active learning strategy. The writer observes that learning which is planned well and implemented by active learning strategy will be able to solve the lack of students’ motivation in learning. Kata kunci: Kualitas pembelajaran, Pendidikan Kewarganegaraan, Strategi Pembelajaran Aktif